2008
DOI: 10.1039/b718535a
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic production of hydrogen on Ni/NiO/KNbO3/CdS nanocomposites using visible light

Abstract: 3. Enhanced activity is most likely due to effective charge separation of photogenerated electrons and holes in CdS that is achieved by electron injection into the conduction band of KNbO 3 and the reduced states of niobium (e.g., Nb(IV) and Nb(III)) are shown to contribute to enhanced reactivity in the KNbO 3 composites by mediating effective electron transfer to bound protons. We also observed that the efficient attachment of Q-size CdS and the deposition of nickel on the KNbO 3 surface increases H 2 product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(52 citation statements)
references
References 66 publications
1
51
0
Order By: Relevance
“…Therefore, the EDL thickness (k) of alcohol-water solution would decrease when alcohols are added to the water, and the decreased order of the k value is: isopropanol-water solution > ethanol-water solution > methanolwater solution, which is the same as their H 2 evolution rate order. The observation agrees with the previous report [53]. This explains the difference of H 2 evolution rate from different alcohol-water solutions.…”
Section: Effect Of Solvent Type On Photocatalytic H 2 Evolutionsupporting
confidence: 94%
“…Therefore, the EDL thickness (k) of alcohol-water solution would decrease when alcohols are added to the water, and the decreased order of the k value is: isopropanol-water solution > ethanol-water solution > methanolwater solution, which is the same as their H 2 evolution rate order. The observation agrees with the previous report [53]. This explains the difference of H 2 evolution rate from different alcohol-water solutions.…”
Section: Effect Of Solvent Type On Photocatalytic H 2 Evolutionsupporting
confidence: 94%
“…A co-catalyst, serving as an electron trap, is generally required to assist water reduction for H 2 production. 60,[65][66][67] Platinum is generally used as a co-catalyst for H 2 generation. [68][69][70] Auxiliary experiments showed that in situ photodeposition of Pt did not promote the H 2 evolution rate for either catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to sulfides and phosphides, several Ni-based oxides and hydroxides, such as NiO, NiO x and Ni(OH) 2 , are also well-known as highly active cocatalysts after being integrated with semiconductors for photocatalytic H 2 production [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77], as summarized in Table 3. For example, Chen et al showed that in situ photodeposition of NiO x on CdS could enhance its photocatalytic H 2 generation activity [63].…”
Section: Ni-based Oxides and Hydroxide Cocatalysts For H 2 Evolutionmentioning
confidence: 99%
“…In particular, Ni-based materials demonstrate excellent activity and have received much attention as H 2 -evolution cocatalysts. Many kinds of Ni-based cocatalysts, such as metallic Ni [38][39][40][41][42][43][44][45][46][47][48][49], sulfides [50][51][52][53][54][55][56][57][58][59][60][61], phosphides [62], oxides [63][64][65][66][67][68][69], hydroxides [70][71][72][73][74][75][76][77], hydrogenases [78][79][80][81], as well as molecular complexes [81][82][83][84][85][86]…”
Section: Introductionmentioning
confidence: 99%